Homecare services - Idris, Zakwan; Mahat, Nurliyana; Md Zin, Muhamd Zulfikri; Abd Rahman, Nuraisyah; Ahmad Norazizi, Nursyaqirin (2014)
Homecare Services is a company that supplies various services designed to help people with problems at home. The business is strategically located at 333, Ground Floor, Jalan S2, B12 Uptown Avenue, Seremban 2, 70300 Seremban, Negeri Sembilan, Malaysia, chosen for its central position amidst numerous residential areas. The company operates with five members holding distinct positions: General Manager, Administration Manager, Financial Manager, Marketing Manager, and Operation Manager. The total capital is derived from members' contributions—RM 6,000 from four members and RM 16,000 from the General Manager—supplemented by a RM 30,000 loan from CIMB Bank. Homecare Services majorly promotes home-based services including painting, renovation, housekeeping, and wiring services.